A Quaternary marine tephrostratigraphic record of New Zealand's explosive volcanism: integration of medial and distal to ultra-distal marine tephra inventories - Pank, Katharina; Kutterolf, S.; Schindlbeck-Belo, J. C.; Hopkins, J. L.; Wang, K. -L.; Lee, H. -Y.; Schmitt, Axel Karl (Journal of volcanology and geothermal research, 2025)
Explosive volcanism is characteristic for New Zealand's Taupō Volcanic Zone (TVZ) and precursory arcs. Yet, complex field relationships hinder the establishment of continuous explosive eruption records. Marine environments preserve deposits of explosive volcanic eruptions, leading to comprehensive, continuous and stratigraphically reliable archives of past eruptions. Here, we present an extended and comprehensive marine tephrostratigraphy of New Zealand's explosive Quaternary volcanism and show how it can be used as a framework for global tephra studies. We analysed major and trace element glass shard compositions (EMP and LA-ICP-MS) of 546 Quaternary marine tephra samples from IODP Exp. 375/372, ODP Leg 181, IODP Leg 329 and DSDP Leg 90 (south-) east of New Zealand. A combined approach of geochemical fingerprinting and stratigraphic context revealed 331 primary marine tephra layers, further correlated across the study area resulting in 165 individual Quaternary volcanic events being identified. Thirty-three of these volcanic events were further assigned to known onshore deposits (e.g. Taupō tephra, Rotoehu ash, Hikuroa Pumice member, and Welcome Bay Ignimbrite). The continuous marine volcanic time series of New Zealand's explosive volcanism provides new evidence for the temporal transition from Coromandel Volcanic Zone to TVZ volcanism, and yields the most accurate repose times of Quaternary volcanism to date (1:12 kyr between <1.6 Ma, and 1:38 kyr between 2.6 and 1.6 Ma). Furthermore, the marine volcanic record shows examples, like the 53 kyr-lasting pulsed volcanic activity associated with the Kidnappers-B/Potaka tephra eruptions, for very large eruptions occurring as eruptive sequences rather than as one continuous event.